2016
DOI: 10.1002/pi.5243
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation of polymer mixtures driven by photochemical reactions: current status and perspectives

Abstract: Phase separation of polymer mixtures induced by photo-crosslinking and photopolymerization is summarized from the viewpoint of competing interactions in polymeric systems. First, the kinetics of photo-crosslinking and photopolymerization are reviewed with particular emphasis on the Trommsdorff − Norrish effect in polymerization, which leads to the formation of a bimodal distribution of molecular weight at long irradiation time. The emergence of a very large molecular weight and the characteristic time for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 95 publications
3
65
1
Order By: Relevance
“…Here, we demonstrate that by using purposely formulated resins, material phases within objects can be controlled using vat polymerization. The method utilizes polymerization-induced phase separation (PIPS), a process previously used to generate 2D patterns in holographic polymerization 24 29 . Exploiting concomitant changes in the thermodynamics of mixing that occur during polymerization, as well as spatio-temporal variations in monomer to polymer conversion, materials can be spatially directed towards the surface of the 3D printed object.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrate that by using purposely formulated resins, material phases within objects can be controlled using vat polymerization. The method utilizes polymerization-induced phase separation (PIPS), a process previously used to generate 2D patterns in holographic polymerization 24 29 . Exploiting concomitant changes in the thermodynamics of mixing that occur during polymerization, as well as spatio-temporal variations in monomer to polymer conversion, materials can be spatially directed towards the surface of the 3D printed object.…”
Section: Introductionmentioning
confidence: 99%
“…We found that Φ is largely non‐linear, which is similar to the evolution of W (after a slow increase, Φ increases quickly at a certain time and then levels off) (Figure a). This autoacceleration of the reaction is plausibly due to the Trommsdorff–Norrish effect that is caused by a dramatic decrease in the rate constant for termination, which is associated with an increase in the viscosity of the polymerizing mixture . Therefore, similar to the analysis of W (Figure f), Φ was fitted to the sigmoid function (solid curves in Figure a).…”
Section: Resultsmentioning
confidence: 91%
“…Presented herein is a numerical study of isothermal spinodal decomposition of a very viscous ternary liquid mixture in the limit of zero fluidity coefficient (further addressed below), following a thermal quench from a stable state in the one-phase region to an unstable location within the tie triangle of its phase diagram. Although our attention in this work will be restricted to nonreactive (symmetric) ternary liquid mixtures, it should be acknowledged that the behavior of reactive (not necessarily symmetric) ternary mixtures has received considerable attention over the past two decades [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. In fact, even though spinodal decomposition in a number of reaction-diffusion systems is usually triggered by a thermal or compositional quench, actually the necessary displacement from a stable state in the one-phase region into the spinodal range can also occur by reaction, e.g., polymerization of a monomer when the polymer being formed is incompatible with one or more of the other components in the mixture.…”
Section: Introductionmentioning
confidence: 99%